Intravitreal aflibercept for diabetic macular edema: structural and functional improvements - Zhang, Chuanhe; Chen, Tianyu; Jia, Ru; Gong, Di; Liu, Zhigao; Wu, Changlong; Shu, Xiangwen; Han, Fangju; Gong, Bin (Frontiers in Medicine, 2025)
IntroductionThe aim of this study was to evaluate the changes in macular structure and visual function of patients with diabetic macular edema (DME) after intravitreal aflibercept injection.MethodsTwenty-five patients (43 eyes) diagnosed with DME were included in this study. All patients underwent aflibercept monthly for 3 months. The study’s endpoints included the best corrected visual acuity (BCVA), central retinal thickness (CRT), fovea avascular zone (FAZ) area, vessel density of superficial retinal capillary plexus (SVD), vessel density of deep retinal capillary plexus (DVD), mean light sensitivity (MLS), 2° fixation rate (P1) and 4° fixation rate (P2).ResultsBefore treatment and after the third treatment, the LogMAR BCVA was 0.69 ± 0.27 and 0.40 ± 0.18, the CRT was 471.10 ± 159.93 μm and 319.84 ± 113.51 μm, the MLS was 18.14 ± 3.97 dB and 21.68 ± 3.55 dB, P1 was 69 (47, 87)% and 88 (72, 92)%, and P2 was 90 (83, 97)% and 97 (93, 99)%, respectively. After treatment, CRT decreased, BVCA, MLS, and fixation stability improved (all p < 0.001). Post-treatment, FAZ area, SVD, and DVD showed no significant changes (all P > 0.05). MLS was negatively correlated with LogMAR BCVA and CRT, and positively correlated with P1 and P2.ConclusionIn short term, aflibercept was effective in reducing CRT and improving BCVA, MLS, and fixation stability in DME patients.